2015
DOI: 10.1111/aec.12227
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat on the germination of sclerophyllous forest species in the highlands of Madagascar

Abstract: International audienceThe effects of fire on germination have been extensively studied in many ecosystems. Several studies have shown that plant species in ecosystems frequently exposed to fire can survive through two main mechanisms: vegetative regeneration (re-sprouts) and recruitment of new individuals from a fire-resistant seed bank. In Africa, an increase in temperature can break seed dormancy and stimulate germination of some herbaceous and woody species. In Madagascar, the once widespread highland ecosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…The timing of fire occurrence is also relevant to determine the damages to leafing, flowering, fruiting and/or germination processes, impacting seedlings and reducing recruitment, as well as favoring specific groups of species that are fire tolerant or fire resistant (Alvarado et al, 2015(Alvarado et al, , 2014Hoffmann, 1998). The peak in active fires, observed on MODIS data from Serra do Cipó between the end of the dry season and the beginning of the wet season (September and October), is consistent with other cerrado studies.…”
Section: Discussionsupporting
confidence: 85%
“…The timing of fire occurrence is also relevant to determine the damages to leafing, flowering, fruiting and/or germination processes, impacting seedlings and reducing recruitment, as well as favoring specific groups of species that are fire tolerant or fire resistant (Alvarado et al, 2015(Alvarado et al, , 2014Hoffmann, 1998). The peak in active fires, observed on MODIS data from Serra do Cipó between the end of the dry season and the beginning of the wet season (September and October), is consistent with other cerrado studies.…”
Section: Discussionsupporting
confidence: 85%
“…microrefugia and climate change (Cooper et al 2011;Keppel et al 2012;Ashcroft and Gollan 2013;Brendonck et al 2014;Mee and Moore 2014;Barrett and Yates 2015), the evolution of trees (Raven and Andrews 2010;Cramer 2012), clonality (Binks et al 2015), the occurrence of OCBISs (old, climatically buffered, infertile seascapes - Langlois et al (2012), significant gaps in Darwinian evolutionary theory (Hopper and Lambers 2009), old salt lake systems (Bui et al 2014a, b), and evolution of novel aquatic traits (Tuckett et al 2010;Davies and Stewart 2014). Seed biological studies are beginning to explore the relevance of Ocbil theory to their discipline (Tuckett et al 2010;Hidayati et al 2012;Wilman et al 2014;Alvarado et al 2015b;Edwards et al 2015;Ribeiro et al 2015).…”
Section: Citation Review Areas Of Focus In the Literature And Summarmentioning
confidence: 99%
“…Alvarado et al (2014) found that forest fragments with apparently less‐frequent fire regimes showed greater tree diversity and sapling density, though fire frequency and management regime were not directly measured in this study. When assessing individual species to investigate the mechanism of this observed hindered post‐fire regeneration, Alvarado et al (2015) found that the seeds of many native highland tree and shrub species did not germinate in response to heat treatments meant to simulate fire. They found a modest ability among some native species to survive exposure to high heat, though it was not clear how this degree of fire tolerance compared to similar biogeographic regions outside of Madagascar.…”
Section: Resultsmentioning
confidence: 99%